Role of Calcium Levels in Pregnant Women with Pre-Eclampsia and Severe Pre-Eclampsia - Sara Khan; Nusrat Noor; Rabiya Akbar; Urooj, Uzma; Sadaf Zohra; Tooba Khan (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the association between hypocalcemia and pre-eclampsia.Study Design: Case-control study.Place and Duration of Study: Department of Obstetrics Gynaecology, Pak Emirates Military Hospital, Rawalpindi Pakistan, from Jan to Jul 2019.Methodology: A total of 90 women, (45 with pre-eclampsia and 45 with normotensive) aged 18-40 years, were included. In all patients, 5ml of venous blood was collected and sent to an institutional pathology laboratory for serum calcium level measurement. Hypocalcemia was noted in the patients.Results: The mean gestational age in the Case-Group was 31.40±1.64 weeks, and in the Control-Group was 31.51±1.69 weeks. The mean BMI in the Case-Group was 24.94±4.39 kg/m2, and in the Control-Group was 24.24±4.61 kg/m2. The mean serum calcium levels in the Case-Group were 5328.73±2638.70 ng/ml, and in the Control-Group were 8630.03±1099.26 ng/ml. In our study, the frequency of hypocalcemia in women with pre-eclampsia (Case Group) was found to be 16(36.56%) compared to only 04(8.89%) in normotensive (Control Group) women with a p-value of 005 and Odds ratio of 5.66 which shows a positive association of hypocalcemia with pre-eclampsia.Conclusion: This study concluded that the frequency of hypocalcemia in pre-eclampsia women is very high, which shows a positive association between hypocalcemia and pre-eclampsia.